2013
DOI: 10.5455/msm.2013.25.113-117
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reporting, Attitudes and Knowledge About the Stab Incidents and Professional Risk of Viral Infection among Health Care Professionals in Primary Health Care

Abstract: Conflict of interest: none declared.GoalThe goal of the research is to determine the relationship between frequency and reporting of stab incidents, attitudes and knowledge about stab incidents and occupational risk for transmission of viral infection with HBV, HCV or HIV among health care professionals employed in primary health care.Material and methodsConducted is prospective, cross-section study by questionnaires in 2012. The survey included health professionals in Primary Health Care Center in Tuzla. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
3
4
0
3
Order By: Relevance
“…In the study by Salzer et al [27] time pressure and lack of experience were the most frequent causes of NSIs, while in other studies the main reason for occupational exposure was a sudden movement of the patient during the procedure [28]. The same reasons as in our study were obtained by Bećirević et al: being in rush, patient’s unpredictable reaction and decrease in concentration [29].…”
Section: Discussionsupporting
confidence: 83%
“…In the study by Salzer et al [27] time pressure and lack of experience were the most frequent causes of NSIs, while in other studies the main reason for occupational exposure was a sudden movement of the patient during the procedure [28]. The same reasons as in our study were obtained by Bećirević et al: being in rush, patient’s unpredictable reaction and decrease in concentration [29].…”
Section: Discussionsupporting
confidence: 83%
“…The present study showed that there was a significant positive correlation between temporal demand and NSIs such that increased temporal demand led to increased NSIs rate among the participants. This finding is also in agreement with other researches (32)(33)(34). Nurses who work in hospitals have to face a disproportionate ratio between demands and resources, leading to increased likelihood of occupational stress.…”
Section: Discussionsupporting
confidence: 93%
“…Reporting and documenting incidents is one of the basic steps to preventing infectious diseases. 19 Lack of reporting of exposure increases the likelihood of infection. In developed contraries, 58% of such injuries are reported.…”
Section: Discussionmentioning
confidence: 99%